Enhancement of strain-rate sensitivity and shear yield strength of a magnesium alloy processed by high-pressure torsion. (1st January 2015) - Choi, In-Chul; Lee, Dong-Hyun; Ahn, Byungmin; Durst, Karsten; Kawasaki, Megumi; Langdon, Terence G.; Jang, Jae-il
Abstract : A Mg–Zn–Zr alloy was processed by high-pressure torsion for up to 2 turns at room temperature to produce significant grain refinement together with enhanced plasticity and strength. Measurements were performed to determine the strain-rate sensitivity, shear yield strength and activation volume as a function of the processing conditions. The results suggest there is a significant contribution from grain boundary sliding to the flow process and the onset of plasticity is associated with heterogeneous dislocation nucleation.